KAJIAN PENURUNAN Ca DAN Mg DALAM AIR LAUT MENGGUNAKAN RESIN - Kimia, Teknik (Jurnal Teknik Kimia, 2008)
Salt is one of the most important thing in our daily life. Salt witch produce by farmer to consumed used haven’t the quality of salt ingredients. The aim of this research is to enchange the quality ofsalt ingredient from sea water by using ion exchange methode. The sea water from storage tankflow to ion exchange column with flow rate certain. Resin Dowex -50 weight 1000 gr is used inthis research .Product from resin column analyzed each hours. The flow rate and contact time are varied . Early consentration from sea water : Ca2+ : 253.8 mg/l and Mg 2+ : 1079.4 mg/ l. Theresult show that contact time in the resin column are very important in Ca and Mg ions reduction.,there fore the velocity ( debite ) needs to be measured to quaranty that the contact time hasproduce the massiv procentage amount. Reduction of Ca ion good relative at flow tae 5 l/ hour at5 hours , the consentration Ca ion is 53.11 %. For Mg ion , consentration reache 43.69 % at flowrate 10 l/ hours.  Key words :sea water, resin, ion exchange